SOSIAL DALAM KEHIDUPAN MASYARAKAT - Hutabarat, Dany Try Hutama; Darmawan, Khairunnisa; Hassymi, Aldi Prayoga; Juwita, Nadila Rahma; Putri, Julia Rahma; Nasution, Adenisya; Siregar, Mia Audina; Fawzan, Rudu; Dewi, Yulia; Hidayat, Riyan Fikqri (Nusantara Hasana Berdikari, 2022)
A social group is a collection of people who share a common sense of membership and interact with each other. Social groups are created by community members for the community itself with various types or types according to the goals or needs of the group itself. Where social groups play a role in shaping the personality and influencing the behavior of its members.